(untitled) (Boletin Médico de Postgrado, 2025)
To determine the presence of peripheral obstructive arterial disease (PAD) in patients with chronic kidney disease (CKD) through the ankle-brachial index (ABI) of the Internal Medicine Department of the Hospital General Universitario Dr. Luis Gómez López during the period june-august 2023, a descriptive cross-sectional study was carried out with 35 patients where a predominance of the age group of 61 to 70 years (34%) and female sex (62%) was observed; 40% of the patients showed CKD stage IIIa and PAD grade III, 100% of the patients presented symptoms corresponding to femoropopliteal arterial territory, 51% infrapopliteal and 6% aortoiliac. With respect to ABI, 60% of the patients presented abnormal or elevated values.